Precautionary saving and precautionary wealth - Christopher D. Carroll; Miles S. Kimball (The Johns Hopkins University, Department of Economics, 2006)
This is an entry for The New Palgrave Dictionary of Economics, 2nd Ed.
Keywords: 330; Precautionary saving; prudence; consumption function; buffer stock saving; Sparen; Kassenhaltungsansatz; Vermögen; Gesamtwirtschaftliche Konsumfunktion; Theorie